2005
DOI: 10.1111/j.1745-4514.2005.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Changes in Myofibrillar Proteins of Goat Skeletal Muscles

Abstract: Postmortem changes at 5C in myofibrillar proteins of longissimus dorsi (LD), biceps femoris (BF), semimembranosus (SM) and semitendinosus (ST) muscles and myofibrillar structure of LD muscle of goat were investigated. Muscle samples were immediately collected after killing, and from carcasses stored at 5C for 3, 6, 9, 12 and 20 days. The sodium dodecyl sulfate‐polyacrylamide gel electrophoresis of myofibrils indicated the appearance of a 30 kDa component, depending on the type of the muscles. A new 55 kDa comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
4
18
1
1
Order By: Relevance
“…This fact has been described by Engel and Banker (1986) in some myopathies in which autophagic mechanisms are excited. However, it has not been described in the above mentioned studies in fish, probably due to that the cited studies were carried out on the first post-mortem stages; neither in mammals, where some post-mortem studies were performed in more advanced stages (Nagaraj et al, 2005;Taylor et al, 1994;Taylor & Koohmaraie, 1998). In the present study autophagic vacuoles increased gradually from 5 days on.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…This fact has been described by Engel and Banker (1986) in some myopathies in which autophagic mechanisms are excited. However, it has not been described in the above mentioned studies in fish, probably due to that the cited studies were carried out on the first post-mortem stages; neither in mammals, where some post-mortem studies were performed in more advanced stages (Nagaraj et al, 2005;Taylor et al, 1994;Taylor & Koohmaraie, 1998). In the present study autophagic vacuoles increased gradually from 5 days on.…”
Section: Discussioncontrasting
confidence: 74%
“…At these advanced stages hexagonal arrangement of sea bream was less apparent and the fragmentation of the myofibers increased. In mammals, myofibrillar fragmentation increased continuously throughout the storage, and it occurred at the level of I-band (Nagaraj, Anilakumar, & Santhanam, 2005;Taylor et al, 1994;Taylor & Koohmaraie, 1998). In the present study, the fragmentation of the myofibrils appeared at different levels of the sarcomeres, although I-band showed the highest and more frequent alterations.…”
Section: Discussionmentioning
confidence: 63%
“…Myofibril fragmentation index has been used as an indicator of postmortem proteolysis in various and species (Lametsch et al. 2007) as it accounts for differences in the rate of postmortem tenderization of meat (Nagaraj et al. 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Myofibrillar fragmentation index has been used as an indicator of postmortem proteolysis in various types of meat (Lametsch et al, 2007) and account for differences in the rate of postmortem tenderization of meat (Nagaraj et al, 2005). The latter authors concluded that structural changes occurring in meat after slaughter are generally believed to be caused by interactions of myofibrillar proteins in the muscle.…”
Section: Myofibrillar Fragmentation Indexmentioning
confidence: 99%